Kualitas Air dan Status Ekosistem Terumbu Karang (Coral Reef) di Perairan Pesisir Kampung Holtekam Distrik MuaraTami Kota Jayapura - Mandey, Vera Kosntansie; Wanimbo, Efray; Ayer, Popi Ida Laila; Barapadang, Barnabas (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2022)
Holtekam village has potential resources in coastal waters. Potential coastal resources in the waters of Kampung Holtekam include coral reefs and fish. The waters of Kampung Holtekam become a source of livelihood for fishermen to find fish and become a tourist destination for various communities. Population growth and development continues to grow and develop in the coastal area of Kampung Holtekam. This has a negative impact on the waters of Kampung Holtekam. Based on the above, it is suspected that the water quality of Holtekam Village has decreased and the health of the coral reef ecosystem is also disturbed. This study aims to determine the condition of the waters based on physical and chemical factors and to determine the health status and condition of coral reefs in the waters of Holtekam Village, Muara District. Water quality data collection techniques are carried out in situ at 5 data collection points which are considered representative of the area around coral reefs and to obtain data and information on coral reef ecosystems using the Point Intercept Transec (PIT) method (Manuputty and Djuwariah. (2009). Analysis of the data in this study, the water condition data obtained were analyzed descriptively and compared with the Decree of the Minister of the Environment No. 51 of 2004 concerning Water Quality Standards for Marine Biota. Coral reef data obtained, analyzed the percentage of coral reef cover following the Manuputty and Djuwariah formula (2009). From the research that has been done it can be concluded that the water quality of Kampung Holtekam is based on the Decree of the Minister of Environment ganHidup Number 51 (2004) concerning water quality standards for marine biota, water quality parameters for temperature, DO and pH are still suitable for coral reef growth. Unless brightness, current speed and salinity do not match accordingly. The percentage of coral reef cover at point 1 is 22%, point 2 is 14%, point 3 is 26%, point 4 is 26% and point 5 is 40%.Shows the condition of the coral reefs in the waters of Kampung Holtekam in a damaged to moderate condition.